2012
DOI: 10.1007/s12288-012-0214-3
|View full text |Cite
|
Sign up to set email alerts
|

Turnaround Time (TAT): Difference in Concept for Laboratory and Clinician

Abstract: Lab investigations are essential in patient management and qualities of the tests reports are emphasized. But there is another aspect of quality which is often overlooked and that is timeliness which is expressed as turnaround time (TAT). Mostly the laboratory services are directed at providing a rapid, reliable report at a reasonable cost. However, most laboratories put undue stress on only reliability, where as the clinician gives more stress on how soon (TAT) a report would be available to them. There is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 8 publications
0
38
0
1
Order By: Relevance
“…Turn-around time is one of the most perceptible aspects noted by clinicians with respect to laboratory services 10 , 12 and is frequently used to gauge laboratory service performance. 9 It can also be used by the laboratory service provider to appraise efficiencies across a network of testing facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turn-around time is one of the most perceptible aspects noted by clinicians with respect to laboratory services 10 , 12 and is frequently used to gauge laboratory service performance. 9 It can also be used by the laboratory service provider to appraise efficiencies across a network of testing facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory test TAT depends on the nature of test, the clinical significance and time to clinical intervention. 10 , 12 For example for CD4 services, determining an acceptable local TAT target is based on the standard of care for enrolling patients onto ART. In South Africa, this equates to ART initiation within 14 days of CD4 testing or seven days where a CD4 is < 200 cells/µL.…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, somewhat similar to a TAT for the laboratory report, the TAT for a BT should be calculated from the time a physician orders a BT to the time the patient starts receiving the BT. [6]…”
Section: Introductionmentioning
confidence: 99%
“…The definition of TAT that needs to be applied should be based on the type of patient served (intensive care unit/emergency/casualty service), priority (STAT/urgent or routine service). They concluded that hospitals need to evolve their own TAT in consultation with both the laboratory personnel and the clinicians and clients (the users) for using TAT as a quality parameter for the laboratory services 7…”
Section: Introductionmentioning
confidence: 99%